Macroeconomics: A Neoclassical Introduction. - Smith, Clifford W.; Miller, Merton H.; Upton, Charles W. (Journal of Finance, 1975)
Merton Miller, winner of the 1990 Noble Prize for Economics, is the Robert R. McCormick Distinguished Service Professor in the Graduate School of Business at the University of Chicago.